Executive Summary - Princes, Elfindah (Journal of Multidisciplinary Issues, 2024)
As the Chief Editor of the Journal of Multidisciplinary Issues, I am honored to present this special edition that explores the profound impacts of emerging technologies, particularly artificial intelligence (AI), on various aspects of society, education, and consumer behavior. This issue features a diverse collection of research papers that provide critical insights into the challenges and opportunities presented by AI and digital platforms. In "Impact of AI-Generated Content on AI Technology: Exploring Model Collapse and Its Implications," Elfindah Princes investigates the phenomenon of "model collapse" within Generative Adversarial Networks (GANs) when trained using AI-generated content. The study introduces new concepts such as "Model Autography Disorder" (MAD) and "Habsburg AI," shedding light on the risks of AI self-consumption and its broader implications for AI-driven systems. The research underscores the necessity for stricter guidelines on using AI-generated content in training models to prevent quality degradation and ensure the sustainability of AI systems​ Elfindah Princes also contributes to this edition with her research on "The Impact of Online Platforms on Generation Z's Learning Styles and Educational Outcomes." This study examines the relationship between material comprehension and satisfaction among Generation Z learners using online platforms. The findings reveal that higher levels of material comprehension lead to greater satisfaction, emphasizing the importance of motivation in enhancing both comprehension and satisfaction. The study highlights the need for educators to focus on designing online learning experiences that foster active engagement and critical thinking​ In another significant contribution, Elfindah Princes and Suppanunta Romprasert explore the challenges posed by AI-generated content in "Navigating the Challenges of AI-Generated Content: Examining Public Trust, Accuracy, and Ethical Implications." The study reveals a nuanced relationship between AI usage and public trust, noting that while AI can influence trust, its impact is currently limited by issues such as model collapse and the accuracy of AI-generated information. The research calls for stronger human oversight, transparency, and ethical guidelines to enhance the reliability of AI content and restore public trust in online information​ Collectively, the studies in this edition highlight the critical need for a balanced approach to integrating AI and digital technologies into various sectors. They underscore the importance of maintaining ethical standards, enhancing transparency, and ensuring human oversight to mitigate potential risks and maximize the benefits of these technologies. As AI continues to evolve, these insights will be invaluable for guiding its responsible and sustainable development.